Hubungan Disiplin Kerja dan Komitmen Kerja dengan Kinerja Guru PAI di SMA se-Kabupaten Pidie - Aulia Rahmat (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
Teachers in the organization are a very important factor in improving the quality of an educational institution. Teachers are required to have high performance. Performance is closely related to the discipline and work commitment of a teacher. Therefore, the research aims to analyze the relationship of work discipline and work commitment to the performance of Islamic Religious Education teachers in SMA in Pidie district. This research is a field research (quantitative field study) that is direct observation on several variables of the object under study. The population in this research is all PAI teachers in SMA Pidie district that is 63 people. The entire population sample by the method of saturated sampling technique. Methods of data collection are observation, documentation, and questionnaire. Data were analyzed using SPSS statistics version 21. The results showed that: 1) The relationship of work discipline to the performance of PAI teachers in SMA Pidie district have a positive effect. 2) Relation of work commitment to teacher performance also has positive effect. 3) The relationship of work discipline and work commitment together affect the teacher performance, seen from the F-count is 6.731 greater than F table 2.85 or probability 0.000, below the value of significance 0.05, means the variable discipline and work commitment in simultaneous effect on teacher performance. The amount of influence is obtained from Adjusted Ratio of 0,680, that independent variable that is work discipline and work commitment able to explain the dependent variable is performance equal to 68% while the rest equal to 32% explained by other variables outside this research model.